Measures for assessing the productivity of sheep and goats - Peacock, C.P. (Elsevier, 1987)
Describes a two year study of sheep and goat production on Maasai group ranches in Kenya. Reviews measures of output used by ILCA and others, and assesses the advantage and disadvanteges of each type of measurement and proposes new indices of production and methods for analysis.